STRATEGI KOMUNIKASI POLITIK DALAM PENCITRAAN PARTAI POLITIK DAN CALON LEGISLATIF PADA PEMILIHAN UMUM TAHUN 2024 Di KABUPATEN BANYUWANGI - Putra Hari Iryanto; Relin D.E; I Nyoman Ananda (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
The arrangement of party images in this thought is taken from research consideration of cases of political communication methodology carried out by the Party and administrative candidates ahead of the administrative race contestation in Banyuwangi Government in 2024 with one central point in the DAPIL V area includes the Tegalsari Region, Gambiran Region and Cluring Region. Now, they are eager to make their presence known and shape the image as something unused reformist authoritative parties and candidates who are equal to other parties, get the thinking the efforts of the Party and its authoritative candidates to shape a modern image or an old fashioned party. The problem detailed in this question is as follows: (1) How is the situation political communication in the image of political parties and administrative candidates in the 2024 joint decision in the Banyuwangi Regional Regulations?. (2) What is the function of political communication in the image of political parties and legislative candidates in the 2024 Election in the Banyuwangi Government?. (3) What is itpolitical communication suggestions in the picture of political parties and An authoritative candidate in the 2024 joint decision in the Banyuwangi Regional Regulations?.The hypothesis used to analyze the problem is the Motivational Setting Hypothesis, Constructivist Hypothesis,  Explanatory Hypothesis. Information was collected using nonparticipant perception procedures, in-depth interviews, documentation studies, and written thoughts, witnesses are selected using deliberate examination and technique of investigating subjective graphic information with the method of deriving, information introduction. , and draw conclusions. Based on information searches, it was found: (1) Forms of Political Communication in the Description of Political Parties and the Legislature Candidates in the 2024 General Decision in Banyuwangi Regency. (2) Employment Political Communication in the Image of Political Parties and Administration Candidate in the 2024 Common Race in Banyuwangi Regency. (3) Suggestions Political Communication in the Image of      political Parties and Administration Candidates in the 2024 General Decision in Banyuwangi Regency.